Avaliação do efeito do alho (Allium sativum L.) sobre o colesterol plasmático em coelhos com hipercolesterolemia induzida - Klassa, B. [UNESP] (2013)
The use of plants to treat diseases or even to cure them is a high diffused popular tradition, and several studies discuss the therapeutic and pharmacological properties of garlic in the reduction of hyperlipidaemias. The objective of the present study was to investigate the influence of the aqueous extract of garlic (Allium sativum) to treat the serum cholesterol of rabbits with experimental hypercholesterolemia. The animals were divided into G1 (control group) and G2 (group treated with garlic). The experiment was developed according to 3 phases: during the 1st phase, all animals were provided with a regular diet to evaluate the basal cholesterol; during the 2nd phase, all animals received a supplemented diet until the end of the experiment, in order to develop hypercholesterolemia and, in the 3rd phase, the animals on G2 received the garlic treatment. The cholesterol registered on the 1st phase was 39.94 ± 9.57 mg dL-1. On the 2nd phase, there was an increase on the serum cholesterol level in both groups - higher than 100 mg dL-1. Concerning the treatment, the garlic did not reduce the serum cholesterol in rabbits.